Report of the "satisfaction" survey amongst public health services nurses in Port Said - Saverio Bellizzi; Susanna Padrini (BMC, 2021)
Abstract Background There is a paucity of evidence regarding the job experience of nurses in Egypt. An unpublished previous pilot study conducted in the Port Said Technical Nursing Institute, which was based on 36 participants, showed that almost half of nurses were satisfied with their job; on the other hand, nurses indicated low salaries and high work-loads as main reasons for dissatisfaction. We explored job satisfaction of nurses working in public health services of the Port Said Governorate to inform future healthcare policy. Methods A cross-sectional study including nurses from different public health services was conducted. Questionnaires were delivered in a sample of primary health care facilities as well as in the Port Said Governorate public hospital. Following a literature review, eight components were identified as contributors to job satisfaction; two closed questions for each of the eight components and two open questions were devised for a total of 18 questions. Results The final study population consisted of 285 individuals. Almost 40.0% of the participants felt safe in their clinical environment while around 10.0% disagree on this. Almost 70.0% of participants complained about high work-load due to shortage of staff in the respective clinical area. Almost 85.0% of nurses reported that their salary did not cover living cost while only 13.0% indicated earning a fair salary. Almost 60.0% agreed with the fact that they have regular opportunities to develop in their career. Conclusion Increasing job satisfaction among nurses in Egypt is critical to ensure quality of care for patients. Issues such as salary, staffing and cooperation with colleagues deserve specific attention.